Positive electrode material and preparation method thereof, positive plate, lithium ion battery and electric equipment

By forming a spinel phase lithium nickel manganese oxide coating on the lithium cobalt oxide positive electrode material, the problem of poor cycle life of traditional lithium cobalt oxide positive electrode material is solved, and high cycle life and stability under high voltage performance.

CN119480996AInactive Publication Date: 2025-02-18TIANJIN B&M SCI & TECH LTD +1

Patent Information

Application Number
CN202411640748.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional lithium cobalt oxide cathode materials have poor life during circulation, especially under high voltage, which are prone to body-phase structure collapse, oxygen evolution, Co dissolution and surface corrosion, resulting in a degradation of battery circulation performance.

Method used

A positive electrode material is used, which includes a core and a cladding layer covering the surface of the core. The core is composed of lithium cobalt oxide. The cladding layer contains lithium nickel manganese oxide of spinel phase. The chemical formula is LiNixMnyMzO4, and M is selected from certain Elements, 0.38≤x≤0.52, 1≤y≤2, 0.0001≤z≤0.0045. The cladding layer is prepared by calcining the mixture and then crushing it to form a continuous and uniform cladding layer closely bonded to the inner core of lithium cobalt oxide.

Benefits of technology

Through the presence of the cladding layer, a three-dimensional Li+ diffusion channel is provided, which reduces the accumulation of Li+ ions, improves the structural stability and rate performance of lithium cobalt oxide, extends its cycle life, and shows a higher cycle life at high voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480996A_ABST
    Figure CN119480996A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a preparation method thereof, a positive plate, a lithium ion battery and electric equipment, the positive electrode material comprises an inner core and a coating layer covering at least part of the surface of the inner core, the inner core comprises lithium cobalt oxide, the coating layer comprises a lithium nickel manganese oxide containing a spinel phase, the lithium nickel manganese oxide satisfies a chemical formula LiNixMnyMzO4, m is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo, x is larger than or equal to 0.38 and smaller than or equal to 0.52, y is larger than or equal to 1 and smaller than or equal to 2, and z is larger than or equal to 0.0001 and smaller than or equal to 0.0045. The positive electrode material provided by the invention can prolong the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium-ion battery and an electrical device. Background Art

[0002] Secondary batteries represented by lithium-ion batteries have the advantages of high operating voltage, high energy density, good safety and no memory effect, and have achieved great success in the fields of portable electronic devices, electric vehicles and hybrid vehicles. At present, in traditional lithium-ion batteries, lithium cobalt oxide positive electrode materials are widely used due to their advantages such as high theoretical specific capacity, but traditional lithium cobalt oxide positive electrode materials often have the problem of poor cycle life. Summary of the invention

[0003] Based on this, the present application provides a positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium-ion battery and an electrical device, which can improve the cycle life of the lithium-ion battery.

[0004] The first aspect of the present application provides a positive electrode material, comprising a core and a coating layer covering at least a portion of the surface of the core, wherein the core comprises lithium cobalt oxide, the coating layer comprises lithium nickel manganese oxide containing a spinel phase, and the lithium nickel manganese oxide satisfies the chemical formula LiNi x Mn y M z O4, M is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo, 0.38≤x≤0.52, 1≤y≤2, 0.0001≤z≤0.004.

[0005] In some embodiments of the present application, one or more of the following conditions are met:

[0006] (1) The thickness of the coating layer is 30nm~100nm, and can be 30nm~50nm;

[0007] (2) The coating layer covers the surface of the inner core at a coverage rate of 80% to 100%;

[0008] (3) The content of nickel in the coating layer is 500ppm~1000ppm, and can be optionally 500ppm~900ppm;

[0009] (4) The content of manganese in the coating layer is 1000ppm~2000ppm, and can be optionally 1200ppm~1800ppm;

[0010] (5) The content of M element in the coating layer is 450ppm~30000ppm.

[0011] In some embodiments of the present application, one or more of the following conditions are met:

[0012] (1) The average particle size of the positive electrode material is 15 μm to 17 μm;

[0013] (2) The specific surface area of ​​the positive electrode material is 0.1 m 2 / g~0.25m 2 / g;

[0014] (3) The tap density of the positive electrode material is 2.7 g / cm 3 ~3.0g / cm 3 ;

[0015] (4) The compaction density of the positive electrode material is 3.8 g / cm 3 ~4.2g / cm 3 .

[0016] The second aspect of the present application provides a method for preparing a positive electrode material, comprising:

[0017] A mixture containing lithium cobalt oxide, a lithium source, a nickel source, a manganese source and a compound containing a doping element is calcined and crushed to obtain a positive electrode material; the positive electrode material comprises a core and a coating layer covering at least a portion of the surface of the core, the core comprises the lithium cobalt oxide, the coating layer comprises a lithium nickel manganese oxide containing a spinel phase, and the lithium nickel manganese oxide satisfies the chemical formula LiNi x Mn y M z O4, M is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo, 0.38≤x≤0.52, 1≤y≤2, 0.0001≤z≤0.0045.

[0018] In some embodiments of the present application, one or more of the following conditions are met:

[0019] (1) The doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo;

[0020] (2) The mass percentage of the nickel source to the lithium cobalt oxide is 1% to 3.5%;

[0021] (3) The mass percentage of the manganese source to the lithium cobalt oxide is 6% to 12%;

[0022] (4) The nickel source is selected from lithium nickelate, and / or

[0023] The manganese source is selected from lithium manganate; and / or

[0024] The lithium source is selected from one or both of lithium nickel oxide and lithium manganese oxide;

[0025] (5) Based on the mass of the lithium cobalt oxide, the content of the compound containing the doping element is 500ppm~20000ppm;

[0026] (6) The cobalt oxide includes a first cobalt oxide and a second cobalt oxide, the first cobalt oxide has an average particle size of 16 μm to 20 μm, the second cobalt oxide has an average particle size of 3.5 μm to 6 μm, and the mass ratio of the first cobalt oxide to the second cobalt oxide is (3 to 5):1;

[0027] (7) The average particle size of the lithium cobalt oxide is 14 μm to 18 μm;

[0028] (8) The calcination conditions include: heating the mixture from room temperature to a preset temperature and maintaining the mixture at the preset temperature;

[0029] Optionally, the preset temperature is 500° C. to 900° C.;

[0030] Optionally, the insulation time is 5h~18h.

[0031] In some embodiments of the present application, the method for preparing lithium cobalt oxide includes:

[0032] Performing a first sintering and then crushing a first mixture including a first lithium source and a first cobalt source to prepare a first lithium cobaltate;

[0033] The second mixture including the second lithium source and the second cobalt source is subjected to a second sintering and then crushed to prepare a second lithium cobaltate;

[0034] The first lithium cobalt oxide and the second lithium cobalt oxide are mixed to obtain the lithium cobalt oxide;

[0035] Optionally, the mass ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is (3-5):1;

[0036] Optionally, the molar ratio of lithium to cobalt of the first lithium source and the first cobalt source is (1.05-1.1):1;

[0037] Optionally, the molar ratio of lithium to cobalt of the second lithium source and the second cobalt source is (1.05-1.1):1;

[0038] Optionally, the first sintering conditions include: heating the first mixture to 500°C to 900°C at a heating rate of 2°C / min to 10°C / min, keeping the temperature for 4h to 8h, and then heating the first mixture to 1000°C to 1200°C at a heating rate of 2°C / min to 5°C / min, and keeping the temperature for 7h to 12h;

[0039] Optionally, the second sintering conditions include: heating the second mixture to 400°C~800°C at a heating rate of 2°C / min~10°C / min, keeping it warm for 3h~7h, and then heating it to 900°C~1000°C at a heating rate of 2°C / min~5°C / min, and keeping it warm for 5h~9h.

[0040] In some embodiments of the present application, the preparation method satisfies one or more of the following conditions:

[0041] (1) The first mixture further includes a compound containing a first doping element, and the first doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo;

[0042] Optionally, in the first mixture, based on the mass of the first cobalt source, the content of the first doping element is 500 ppm to 15000 ppm;

[0043] (2) the second mixture further includes a compound containing a second doping element, wherein the second doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo;

[0044] Optionally, in the second mixture, based on the mass of the second cobalt source, the content of the second doping element is 500ppm~12000ppm.

[0045] The third aspect of the present application provides a positive electrode sheet, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the second aspect of the present application.

[0046] The fourth aspect of the present application provides a lithium-ion battery, comprising the positive electrode sheet of the third aspect of the present application.

[0047] A fifth aspect of the present application provides an electrical device comprising the lithium-ion battery of the fourth aspect.

[0048] The electrical equipment of the present application includes the lithium-ion battery provided by the present application, and thus has at least the same advantages as the lithium-ion battery.

[0049] In the coating layer of the positive electrode material of the present application, the lithium nickel manganese oxide contains a spinel phase satisfying the above chemical formula, and the spinel phase can provide a three-dimensional Li + Diffusion channel, which helps Li + Ion deintercalation and conduction, reducing Li + The accumulation of ions is conducive to the improvement of the structural stability and rate performance of lithium cobalt oxide. At the same time, the coating layer can effectively isolate the direct contact between lithium cobalt oxide and the electrolyte, thereby reducing the collapse and destruction of the layered structure of lithium cobalt oxide caused by cobalt dissolution and oxygen escape, thereby improving the cycle performance of lithium cobalt oxide and increasing its cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] FIG. 1 is a morphology diagram of the positive electrode material of Example 1 of the present application. DETAILED DESCRIPTION

[0051] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0052] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are for the purpose of describing specific embodiments only and are not intended to limit this application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" are inclusive of the number, and the meaning of "multiple" in "one or more" is more than two.

[0054] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​within the numerical interval is considered to be continuous and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when a numerical interval only refers to integers within the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0055] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0056] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0057] Traditional lithium cobalt oxide positive electrode materials are usually layered structures, which are prone to bulk structure collapse, oxygen evolution, Co dissolution and surface corrosion when charged and discharged at high voltages, resulting in decreased battery cycle performance, rapid capacity decay, and even safety accidents, which seriously hinders its application at high voltages. In order to solve this technical problem, the inventors proposed the following technical solution of this application.

[0058] In a first aspect, the present application provides a positive electrode material, comprising a core and a coating layer covering at least a portion of the surface of the core, wherein the core comprises lithium cobalt oxide, the coating layer comprises lithium nickel manganese oxide containing a spinel phase, and the lithium nickel manganese oxide satisfies the chemical formula LiNi x Mn y M zO4, M is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo, 0.38≤x≤0.52, 1≤y≤2, 0.0001≤z≤0.0045.

[0059] In the coating layer of the above positive electrode material, the lithium nickel manganese oxide contains a spinel phase satisfying the above chemical formula, which can provide a three-dimensional Li + Diffusion channel, which helps Li + Ion deintercalation and conduction, reducing Li + The accumulation of ions is beneficial to the improvement of the structural stability and rate performance of lithium cobalt oxide. At the same time, the coating layer can also effectively isolate the direct contact between lithium cobalt oxide and the electrolyte, thereby reducing the collapse and destruction of the layered structure of lithium cobalt oxide caused by cobalt dissolution and oxygen escape, thereby improving the cycle performance of lithium cobalt oxide and increasing its cycle life. Among them, in the lithium nickel manganese oxide that satisfies the above chemical formula, Mn ions do not participate in the valence change, which can stabilize the structure of the positive electrode material and improve the cycle stability. Ni ions can provide higher specific capacity and higher voltage for the positive electrode material, and improve the cycle life and energy density; Ni and Mn are co-coated and mutually promoted, which can simultaneously improve the capacity and cycle stability of the material; doping element M can make the coating layer more stable, which is conducive to further improvement of the cycle life. Therefore, through the above improvements, the positive electrode material provided in this application can meet the application under high voltage, and it has a higher cycle life under high voltage.

[0060] In some embodiments, the coating layer has a thickness of 30 nm to 100 nm. For example, the coating layer may have a thickness of 30 nm, 32 nm, 34 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 46 nm, 48 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any range thereof; it may be 30 μm to 50 μm. The coating layer thickness is controlled within a suitable range, which can improve the cycle life of the positive electrode material and control the diffusion path of lithium ions within a suitable range, thereby taking into account both rate performance and rate performance.

[0061] In some embodiments, the coating layer covers the surface of the core at a coverage rate of 80% to 100%. For example, the coverage rate can be 80%, 85%, 90%, 95%, 100% or within a range formed by any of the above values. The coating layer covers the surface of the core at a coverage rate controlled within a suitable range, which can effectively reduce the collapse and damage of the layered structure of lithium cobalt oxide caused by cobalt dissolution and oxygen escape, and effectively improve the cycle life of lithium cobalt oxide.

[0062] In some embodiments, the content of nickel in the coating layer is 500ppm~1000ppm. For example, the content of nickel in the coating layer can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm or in the range of any of the above values; it can be 500ppm~900ppm. The content of nickel in the coating layer is controlled within a suitable range, which can provide a higher specific capacity and a higher voltage for the positive electrode material and improve the cycle life; on the other hand, it can reduce the reaction between the nickel content and the electrolyte when it is high, improve the structural stability of the positive electrode material, and further improve the cycle life.

[0063] In some embodiments, the content of manganese in the coating layer is 1000ppm~2000ppm. For example, the content of manganese in the coating layer can be 1000ppm, 1200ppm, 1400ppm, 1600ppm, 1800ppm, 2000ppm or in the range of any of the above values; it can be 1200ppm~1800ppm. The content of manganese in the coating layer is controlled within a suitable range, which can effectively stabilize the structure of the positive electrode material and improve the cycle stability; on the other hand, it can also keep the energy density of the positive electrode material at a high level.

[0064] In some embodiments, the content of the M element in the coating layer is 450ppm to 30000ppm. For example, the content of the M element in the coating layer can be 450ppm, 1000ppm, 5000ppm, 8000ppm, 10000ppm, 15000ppm, 20000ppm, 25000ppm, 30000ppm or within the range of any of the above values. The M element content is controlled within a suitable range, which is conducive to making the positive electrode material have better cycle performance.

[0065] It should be noted that "ppm" in this application refers to one part per million, that is, for every one million parts by weight (or mass) of substance B, there is 1 part by weight (or mass) of substance A; for example, the content of nickel in the coating layer is 500ppm~1000ppm, which means that every 1kg of the coating layer contains 500mg~1000mg of nickel.

[0066] In some embodiments, the average particle size of the positive electrode material is 15 μm to 17 μm. For example, the average particle size of the positive electrode material can be 15 μm, 16 μm, 17 μm, or within a range consisting of any of the above values.

[0067] In some embodiments, the specific surface area of ​​the positive electrode material is 0.1 m 2 / g~0.25m 2 / g. For example, the specific surface area of ​​the positive electrode material can be 0.1m 2 / g,0.15m 2 / g,0.2m 2 / g,0.25m 2 / g or within a range consisting of any of the above values.

[0068] In some embodiments, the tap density of the positive electrode material is 2.7 g / cm 3 ~3.0g / cm 3 For example, the tap density of the positive electrode material can be 2.7 g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 , 3.0g / cm 3 Or within a range consisting of any of the above values.

[0069] In some embodiments, the compaction density of the positive electrode material is 3.8 g / cm 3 ~4.2g / cm 3 For example, the compaction density of the positive electrode material can be 3.8 g / cm 3 , 3.9g / cm 3 , 4.0g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 Or within a range consisting of any of the above values.

[0070] In a second aspect, the present application provides a method for preparing a positive electrode material, which can be used to prepare the positive electrode material of the first aspect of the present application, and may include the following steps:

[0071] A mixture containing lithium cobalt oxide, a lithium source, a nickel source, a manganese source and a compound containing a doping element is calcined and crushed to obtain a positive electrode material; the positive electrode material comprises a core and a coating layer covering at least a portion of the surface of the core, the core comprises the lithium cobalt oxide, the coating layer comprises a lithium nickel manganese oxide containing a spinel phase, and the lithium nickel manganese oxide satisfies the chemical formula LiNi x Mn y M z O4, M is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo, 0.38≤x≤0.52, 1≤y≤2, 0.0001≤z≤0.0045.

[0072] In the above preparation method, lithium cobalt oxide is mixed with a lithium source, a nickel source, a manganese source, and a compound containing doping elements and then calcined, so that a solid solution of lithium nickel manganese oxide can be generated in situ on the surface of the lithium cobalt oxide, so that the coating layer and the lithium cobalt oxide core can be tightly bonded through chemical bonds, and a continuous and uniform coating layer is formed, so that the positive electrode material has very good structural stability, which is conducive to the improvement of its cycle life. In addition, the positive electrode material prepared by the above method of this application has a good cycle life at high voltage, and the preparation process is simple, which is suitable for mass production.

[0073] In some embodiments, the doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo. The addition of doping elements can make the coating layer more stable, which is conducive to further improving the cycle life.

[0074] In some embodiments, the nickel source accounts for 1% to 3.5% by mass of the lithium cobalt oxide.

[0075] In some embodiments, the mass percentage of the manganese source in the lithium cobalt oxide is 6% to 12%.

[0076] In some embodiments, the nickel source is selected from lithium nickelate.

[0077] In some embodiments, the manganese source is selected from lithium manganate.

[0078] In some embodiments, the lithium source is selected from one or both of lithium nickel oxide and lithium manganese oxide.

[0079] In some embodiments, based on the mass of lithium cobalt oxide, the content of the compound containing the doping element is 500ppm to 20000ppm. In this way, the content of the doping element M in the coating layer can be controlled within the appropriate range described in the first aspect of the present application.

[0080] It can be understood that the above “based on the mass of lithium cobalt oxide” means that for every 1 kg of lithium cobalt oxide contained in the mixture, there are 500 ppm to 20,000 ppm of the compound containing the doping element.

[0081] In some embodiments, the cobalt oxide includes a first cobalt oxide and a second cobalt oxide, the first cobalt oxide has an average particle size of 16 μm to 20 μm, the second cobalt oxide has an average particle size of 3.5 μm to 6 μm, and the mass ratio of the first cobalt oxide to the second cobalt oxide is (3 to 5): 1. In this way, the positive electrode material can have a higher compaction density, thereby improving the energy density.

[0082] In some embodiments, the average particle size of the lithium cobalt oxide is 14 μm to 18 μm.

[0083] In some embodiments, the calcination conditions include: heating the mixture from room temperature to a preset temperature, and maintaining the mixture at the preset temperature.

[0084] It is understood that the "room temperature" mentioned in this application refers to a temperature of 25°C to 35°C.

[0085] In some embodiments, the preset temperature is 500°C to 900°C.

[0086] In some embodiments, the insulation time is 5h~18h.

[0087] In some embodiments, the method for preparing lithium cobalt oxide may include the following steps S10-S30:

[0088] S10, performing a first sintering and then crushing a first mixture including a first lithium source and a first cobalt source to prepare a first lithium cobaltate;

[0089] S20, sintering the second mixture containing the second lithium source and the second cobalt source for the second time and then crushing it to prepare a second lithium cobaltate;

[0090] S30, mixing the first lithium cobalt oxide and the second lithium cobalt oxide to obtain the lithium cobalt oxide.

[0091] In some embodiments, the mass ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is (3-5):1.

[0092] In some embodiments, the molar ratio of the lithium element in the first lithium source to the cobalt element in the first cobalt source is (1.05-1.1): 1. For example, the molar ratio may be 1.05: 1, 1.06: 1, 1.07: 1, 1.08: 1, 1.09: 1, 1.1: 1 or within a range of any of the above values.

[0093] In some embodiments, the molar ratio of the lithium element in the second lithium source to the cobalt element in the second cobalt source is (1.05-1.1): 1. For example, the molar ratio may be 1.05: 1, 1.06: 1, 1.07: 1, 1.08: 1, 1.09: 1, 1.1: 1 or within a range of any of the above values.

[0094] The molar ratio of lithium to cobalt is selected within the above range, which can compensate for the lithium loss caused by volatilization or lithium absorption in the sagger during the sintering process, reduce the production of lithium-deficient lithium cobalt oxide, achieve the effect of capacity improvement, and ensure the sufficiency and uniformity of the sintering process.

[0095] In some embodiments, the average particle size of the second cobalt source is 3 μm to 5 μm.

[0096] In some embodiments, the first sintering conditions include: heating the first mixture to 500°C~900°C at a heating rate of 2°C / min~10°C / min, keeping it warm for 4h~8h, and then heating it to 1000°C~1200°C at a heating rate of 2°C / min~5°C / min, and keeping it warm for 7h~12h.

[0097] In some embodiments, the second sintering conditions include: heating the second mixture to 400°C~800°C at a heating rate of 2°C / min~10°C / min, keeping it warm for 3h~7h, and then heating it to 900°C~1000°C at a heating rate of 2°C / min~5°C / min, and keeping it warm for 5h~9h.

[0098] The first sintering and the second sintering adopt a two-stage sintering process respectively, and the two-stage sintering first uses low temperature and then high temperature calcination, which can make the particle structure more stable and the prepared lithium cobalt oxide has better performance.

[0099] In some embodiments, the first mixture also includes a compound containing a first doping element, and the first doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo.

[0100] In some embodiments, in the first mixture, based on the mass of the first cobalt source, the content of the first doping element is 500 ppm to 15000 ppm.

[0101] It can be understood that the above “based on the mass of the first cobalt source” means that for every 1 kg of the first cobalt source contained in the first mixture, 500 ppm to 15000 ppm of the first doping element is contained.

[0102] In some embodiments, the second mixture also includes a compound containing a second doping element, and the second doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo.

[0103] In some embodiments, in the second mixture, based on the mass of the second cobalt source, the content of the second doping element is 500 ppm to 12000 ppm.

[0104] It can be understood that the above “based on the mass of the second cobalt source” means that for every 1 kg of the second cobalt source contained in the second mixture, 500 ppm to 12000 ppm of the second doping element is contained.

[0105] In some embodiments, the heating rate is 2°C / min to 5°C / min.

[0106] In some embodiments, the first lithium source (or the second lithium source) and the first cobalt source (or the second cobalt source) may be mixed in a high-speed mixer to prepare a first mixture (or a second mixture), wherein the mixing process may adopt multi-stage mixing, the speed of the first stage is 200rpm~700rpm, and the speed of the second stage is 800rpm~1000rpm. Multi-stage mixing can ensure uniform mixing of materials, higher mixing efficiency, and less damage to raw material particles.

[0107] In some embodiments, the first lithium source and the second lithium source are each independently selected from one or more of lithium carbonate, lithium nitrate, lithium acetate, lithium hydroxide, lithium oxide, lithium chloride, lithium bromide, and lithium fluoride.

[0108] In some embodiments, the first cobalt source and the second cobalt source are each independently selected from one or more of cobalt trioxide, cobalt hydroxide, cobaltous oxide, cobalt nitrate, cobalt sulfate, and cobalt oxyhydroxide.

[0109] It should be noted that the equipment for calcination or first sintering and second sintering described in the present application can be a muffle furnace, a tunnel furnace, a roller kiln, a tubular furnace or other types of calcination equipment, which is not limited here.

[0110] In a third aspect, the present application provides a positive electrode sheet, comprising the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the preparation method of the second aspect of the present application.

[0111] In a fourth aspect, the present application provides a lithium-ion battery, comprising the positive electrode sheet of the third aspect of the present application.

[0112] In some embodiments, the lithium-ion battery further includes a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, lithium ions are inserted and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0113] In a fifth aspect, the present application provides an electrical device, comprising the lithium-ion battery of the fourth aspect of the present application.

[0114] In some embodiments, the type of the electric device is not particularly limited, and it can be any electronic device known in the prior art. For example, the electric device can include, but is not limited to, power tools, electric cars, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, etc.

[0115] Example

[0116] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0117] Example 1

[0118] (1) Co3O4, Li2CO3, MgCO3 and La2O3 are mixed in a high-speed mixer, and the first stage is operated at 550 rpm for 5 minutes; the second stage is operated at 950 rpm for 20 minutes to obtain a first mixture; wherein the molar ratio of lithium element to cobalt element is 1.08:1; based on the mass of Co3O4, the content of MgCO3 is 1500 ppm of the mass of Co3O4, and the content of La2O3 is 800 ppm of the mass of Co3O4.

[0119] The first mixture was heated to 780°C at a heating rate of 4°C / min in the first stage and kept at the constant temperature for 5 hours; in the second stage, it was heated to 1060°C at a heating rate of 3°C / min, kept at the constant temperature for 8 hours, cooled, and crushed to an average particle size of 19.2 μm to obtain the first lithium cobalt oxide.

[0120] (2) Co3O4, Li2CO3 and TiO2 were mixed in a high-speed mixer, and the first stage was operated at 550 rpm for 5 min; the second stage was operated at 950 rpm for 20 min to obtain a second mixture; wherein the molar ratio of lithium element to cobalt element was 1.05:1; and the content of TiO2 was 500 ppm based on the mass of Co3O4.

[0121] The second mixture was heated to 730°C at a heating rate of 4°C / min in the first stage and kept warm for 5 hours; in the second stage, it was heated to 1000°C at a heating rate of 2°C / min, kept warm for 8 hours, cooled, and crushed to an average particle size of 4.5 μm to obtain a second lithium cobalt oxide.

[0122] (3) Mix the first lithium cobalt oxide, the second lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide and TiO2 in a high-speed mixer, operate the first stage at 500 rpm for 5 minutes, and operate the second stage at 1100 rpm for 30 minutes to obtain a mixture. The first lithium cobalt oxide and the second lithium cobalt oxide are mixed in a mass ratio of 4.5:1 to form lithium cobalt oxide; based on the mass of lithium cobalt oxide, lithium nickel oxide accounts for 3.2% of the mass of lithium cobalt oxide, lithium manganese oxide accounts for 9% of the mass of lithium cobalt oxide, and TiO2 accounts for 600 ppm of the mass of lithium cobalt oxide.

[0123] The mixture was heated to 900°C at a heating rate of 4°C / min, kept at a constant temperature for 8 hours, cooled, and crushed to an average particle size of 15.4 μm to obtain a positive electrode material containing a coating layer, wherein the coating layer contains lithium nickel manganese oxide LiNi 0.4 Mn 1.5 Ti 0.0015 O4.

[0124] Example 2

[0125] (1) Co3O4, Li2CO3, Al2O3 and La2O3 are mixed in a high-speed mixer, and the first stage is operated at 600 rpm for 5 minutes; the second stage is operated at 800 rpm for 20 minutes to obtain a first mixture; wherein the molar ratio of lithium element to cobalt element is 1.06:1; based on the mass of Co3O4, the content of Al2O3 is 1500 ppm of the mass of Co3O4, and the content of La2O3 is 700 ppm of the mass of Co3O4.

[0126] The first mixture was heated to 800°C at a heating rate of 3°C / min in the first stage and kept at the constant temperature for 4 hours; in the second stage, it was heated to 1070°C at a heating rate of 4°C / min, kept at the constant temperature for 9 hours, cooled, and crushed to an average particle size of 18.3 μm to obtain the first lithium cobalt oxide.

[0127] (2) Co3O4, Li2CO3 and ZrO2 were mixed in a high-speed mixer, and the first stage was operated at 600 rpm for 5 min; the second stage was operated at 800 rpm for 20 min to obtain a second mixture; wherein the molar ratio of lithium element to cobalt element was 1.05:1; and the content of ZrO2 was 1000 ppm based on the mass of Co3O4.

[0128] The second mixture was heated to 750°C at a heating rate of 3°C / min in the first stage and kept at the constant temperature for 5 hours; in the second stage, it was heated to 950°C at a heating rate of 1.5°C / min, kept at the constant temperature for 8.5 hours, cooled, and crushed to an average particle size of 4.5 μm to obtain a second lithium cobalt oxide.

[0129] (3) Mix the first lithium cobalt oxide, the second lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, TiO2 and WO3 in a high-speed mixer, and run the first stage at 600 rpm for 5 minutes; and the second stage at 1000 rpm for 30 minutes to obtain a mixture. The first lithium cobalt oxide and the second lithium cobalt oxide are mixed in a mass ratio of 4.2:1 to form lithium cobalt oxide; based on the mass of lithium cobalt oxide, lithium nickel oxide accounts for 3% of the mass of lithium cobalt oxide, lithium manganese oxide accounts for 7% of the mass of lithium cobalt oxide, TiO2 accounts for 500 ppm of the mass of lithium cobalt oxide, and WO3 accounts for 500 ppm of the mass of lithium cobalt oxide.

[0130] The mixture was heated to 870°C at a heating rate of 4°C / min, kept at a constant temperature for 8 hours, cooled, and crushed to an average particle size of 16.3 μm to obtain a positive electrode material containing a coating layer, wherein the coating layer contains lithium nickel manganese oxide LiNi 0.4 Mn 1.4 Ti 0.001 W 0.001 O4.

[0131] Example 3

[0132] (1) Co3O4, Li2CO3, MgCO3, Al2O3 and Nb2O5 are mixed in a high-speed mixer, and the first stage is operated at 500 rpm for 5 minutes; the second stage is operated at 900 rpm for 20 minutes to obtain a first mixture, wherein the molar ratio of lithium element to cobalt element is 1.07:1; based on the mass of Co3O4, the content of MgCO3 is 1200ppm of the mass of Co3O4, the content of Al2O3 is 7000ppm of the mass of Co3O4, and the content of Nb2O5 is 1000ppm of the mass of Co3O4.

[0133] The first mixture was heated to 700°C at a heating rate of 4°C / min in the first stage and kept at the constant temperature for 6 hours; in the second stage, it was heated to 1020°C at a heating rate of 3°C / min, kept at the constant temperature for 8 hours, cooled, and crushed to an average particle size of 17.9 μm to obtain the first lithium cobalt oxide.

[0134] (2) Co3O4, Li2CO3 and La2O3 were mixed in a high-speed mixer, and the first stage was operated at 600 rpm for 5 minutes; the second stage was operated at 800 rpm for 20 minutes to obtain a second mixture, wherein the molar ratio of lithium element to cobalt element was 1.05:1; based on the mass of Co3O4, the content of La2O3 was 1000 ppm of the mass of Co3O4.

[0135] The second mixture was heated to 750°C at a heating rate of 3°C / min in the first stage and kept at the constant temperature for 5 hours; in the second stage, it was heated to 950°C at a heating rate of 1.5°C / min, kept at the constant temperature for 8.5 hours, cooled, and crushed to an average particle size of 4.5 μm to obtain a second lithium cobalt oxide.

[0136] (3) Mix the first lithium cobalt oxide, the second lithium cobalt oxide, lithium hydroxide, nickel oxide, manganese oxide and ZrO2 in a high-speed mixer, operate the first stage at 500 rpm for 5 minutes, and operate the second stage at 1100 rpm for 30 minutes to obtain a mixture. The first lithium cobalt oxide and the second lithium cobalt oxide are mixed in a mass ratio of 3.7:1 to form lithium cobalt oxide; based on the mass of lithium cobalt oxide, lithium nickel oxide accounts for 2.8% of the mass of lithium cobalt oxide, lithium manganese oxide accounts for 7% of the mass of lithium cobalt oxide, and ZrO2 accounts for 750 ppm of the mass of lithium cobalt oxide.

[0137] The mixture was heated to 800°C at a heating rate of 4°C / min, kept at a constant temperature for 8 hours, cooled, and crushed to an average particle size of 16.8 μm to obtain a positive electrode material containing a coating layer, wherein the coating layer contains lithium nickel manganese oxide LiNi 0.39 Mn 1.5 Zr 0.0025 O4.

[0138] Example 4

[0139] The preparation process is similar to that of Example 1, with the main difference being that the mass of lithium nickel oxide in step 3 is adjusted to 3% of the mass of lithium cobalt oxide, and the mass of lithium manganese oxide is adjusted to 6% of the mass of lithium cobalt oxide, so that the thickness of the coating layer is 30 nm.

[0140] Example 5

[0141] The preparation process is similar to that of Example 1, with the main difference being that the mass of lithium nickel oxide in step 3 is adjusted to 3.2% of the mass of lithium cobalt oxide, and the mass of lithium manganese oxide is adjusted to 8% of the mass of lithium cobalt oxide, so that the thickness of the coating layer is 40 nm.

[0142] Example 6

[0143] The preparation process is similar to that of Example 1, with the main difference being that the mass of lithium nickel oxide in step 3 is adjusted to 3.4% of the mass of lithium cobalt oxide, and the mass of lithium manganese oxide is adjusted to 10.5% of the mass of lithium cobalt oxide, so that the thickness of the coating layer is 50 nm.

[0144] Example 7

[0145] The preparation process is similar to that of Example 1, with the main difference being that the content of TiO2 in step 3 is adjusted to 700ppm based on the mass of lithium cobalt oxide, so that the coverage rate of the coating layer on the surface of the inner core is 73%.

[0146] Example 8

[0147] The preparation process is similar to that of Example 1, with the main difference being that the content of TiO2 in step 3 is adjusted to 700ppm of the mass of lithium cobalt oxide, and 500ppm of Y2O3 is added, so that the coverage rate of the coating layer on the surface of the inner core is 81%.

[0148] Example 9

[0149] The preparation process is similar to that of Example 1, with the main differences being that the mass of lithium nickel oxide in step 3 is adjusted to 3.5% of the mass of lithium cobalt oxide, the mass of lithium manganese oxide is 12% of the mass of lithium cobalt oxide, the content of TiO2 is adjusted to 800ppm of the mass of lithium cobalt oxide, and 500ppm of Y2O3 is added to ensure that the coverage rate of the coating layer on the surface of the inner core is 100%.

[0150] Comparative Example 1

[0151] The preparation method is similar to that of Example 1, with the main difference being that the lithium nickel oxide and lithium manganese oxide in step (3) are omitted, so that the prepared positive electrode material has no coating layer.

[0152] Comparative Example 2

[0153] The preparation method is similar to that of Example 1, with the main difference being that in step (3), lithium nickelate is omitted, so that lithium nickel manganese oxide cannot be formed in the prepared coating layer.

[0154] Comparative Example 3

[0155] The preparation method is similar to that of Example 1, with the main difference being that in step (3), lithium manganese oxide is omitted, so that lithium nickel manganese oxide cannot be formed in the prepared coating layer.

[0156] The positive electrode materials prepared in Examples 1 to 9 and Comparative Examples 1 to 3 or the lithium ion batteries further prepared therefrom were subjected to relevant performance tests, and the test results are shown in Table 1 below.

[0157] Among them, the test conditions or test standards for each performance test item are as follows:

[0158] (1) Thickness of coating layer: The thickness of coating layer was observed using a transmission electron microscope (e.g., Hitachi HT7800).

[0159] (2) Covering rate of coating layer: measured using transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX).

[0160] (3) The average particle size can be tested by the following method: using a laser particle size analyzer. The testing instrument can be a Mastersizer 3000 laser particle size analyzer produced by Malvern Instruments Ltd., UK.

[0161] (4) Compaction density: Tested using a compaction density meter with a test pressure of 3 tons (T) and a compaction time of 30 seconds.

[0162] (5) Specific surface area: It can be tested by the following method: Refer to GB / T 19587-2017, use the nitrogen adsorption specific surface area analysis test method, and calculate it using the BET (Brunauer Emmett Teller) method.

[0163] (6) Morphology test: The sample morphology was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM).

[0164] (7) Test of the content of each element in the coating layer: The test was carried out using inductively coupled plasma atomic emission spectroscopy (ICP-OES) method.

[0165] (8) Electrochemical performance

[0166] The positive electrode material is assembled into a CR2032 button cell, wherein the positive electrode sheet is prepared from the positive electrode material, acetylene black and a binder PVDF in a mass ratio of 90:6:4.

[0167] The CR2032 button battery was placed in a high temperature environment of 45°C, charged at 0.1C and discharged at 0.1C for 50 weeks in the voltage range of 3V~4.60V, and the discharge specific capacity at the 50th week was recorded to obtain the capacity retention rate; capacity retention rate = (50-week discharge specific capacity / first discharge specific capacity) × 100%.

[0168] Table 1

[0169]

[0170] Table 2

[0171]

[0172] Combining Table 1 and Table 2 above, it can be seen that compared with Comparative Examples 1, 2, and 3, Examples 1 to 9 have higher charge and discharge specific capacities and capacity retention rates, indicating that when the coating layer includes lithium nickel manganese oxide, the capacity and cycle life of the positive electrode material and the battery can be improved. In addition, it can be seen from Figure 1 that the positive electrode material prepared in the present application is coated more uniformly.

[0173] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0174] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A positive electrode material, characterized in that: The invention comprises a core and a coating layer covering at least a part of the surface of the core, wherein the core comprises lithium cobalt oxide, the coating layer comprises lithium nickel manganese oxide containing a spinel phase, and the lithium nickel manganese oxide satisfies the chemical formula LiNi x Mn y M z O4, M is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo, 0.38≤x≤0.52, 1≤y≤2, 0.0001≤z≤0.0045.

2. The positive electrode material according to claim 1, characterized in that Meet one or more of the following conditions: (1) The thickness of the coating layer is 30nm~100nm, and can be 30nm~50nm; (2) The coating layer covers the surface of the inner core at a coverage rate of 80% to 100%; (3) The content of nickel in the coating layer is 500ppm~1000ppm, and can be optionally 500ppm~900ppm; (4) The content of manganese in the coating layer is 1000ppm~2000ppm, and can be optionally 1200ppm~1800ppm; (5) The content of M element in the coating layer is 450ppm~30000ppm.

3. The positive electrode material according to claim 1 or 2, characterized in that Meet one or more of the following conditions: (1) The average particle size of the positive electrode material is 15 μm to 17 μm; (2) The specific surface area of ​​the positive electrode material is 0.1 m 2 / g~0.25m 2 / g; (3) The tap density of the positive electrode material is 2.7 g / cm 3 ~3.0g / cm 3 ; (4) The compaction density of the positive electrode material is 3.8 g / cm 3 ~4.2g / cm 3 .

4. A method for preparing a positive electrode material, characterized in that: include: A mixture containing lithium cobalt oxide, a lithium source, a nickel source, a manganese source and a compound containing a doping element is calcined and crushed to obtain a positive electrode material; the positive electrode material comprises a core and a coating layer covering at least a portion of the surface of the core, the core comprises the lithium cobalt oxide, the coating layer comprises a lithium nickel manganese oxide containing a spinel phase, and the lithium nickel manganese oxide satisfies the chemical formula LiNi x Mn y M z O4, M is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo, 0.38≤x≤0.52, 1≤y≤2, 0.0001≤z≤0.

004.

5. The preparation method according to claim 4, characterized in that: Meet one or more of the following conditions: (1) The doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo; (2) The mass percentage of the nickel source to the lithium cobalt oxide is 1% to 3.5%; (3) The mass percentage of the manganese source to the lithium cobalt oxide is 6% to 12%; (4) The nickel source is selected from lithium nickelate, and / or The manganese source is selected from lithium manganate; and / or The lithium source is selected from one or both of lithium nickel oxide and lithium manganese oxide; (5) Based on the mass of the lithium cobalt oxide, the content of the compound containing the doping element is 500ppm~20000ppm; (6) The cobalt oxide includes a first cobalt oxide and a second cobalt oxide, the first cobalt oxide has an average particle size of 16 μm to 20 μm, the second cobalt oxide has an average particle size of 3.5 μm to 6 μm, and the mass ratio of the first cobalt oxide to the second cobalt oxide is (3 to 5):1; (7) The average particle size of the lithium cobalt oxide is 14 μm to 18 μm; (8) The calcination conditions include: heating the mixture from room temperature to a preset temperature and maintaining the mixture at the preset temperature; Optionally, the preset temperature is 500° C. to 900° C.; Optionally, the insulation time is 5h~18h.

6. The preparation method according to claim 4 or 5, characterized in that: The preparation method of the lithium cobalt oxide comprises: Performing a first sintering and then crushing a first mixture including a first lithium source and a first cobalt source to prepare a first lithium cobaltate; The second mixture including the second lithium source and the second cobalt source is subjected to a second sintering and then crushed to prepare a second lithium cobaltate; The first lithium cobalt oxide and the second lithium cobalt oxide are mixed to obtain the lithium cobalt oxide; Optionally, the mass ratio of the first lithium cobalt oxide to the second lithium cobalt oxide is (3-5):1; Optionally, the molar ratio of lithium to cobalt of the first lithium source and the first cobalt source is (1.05-1.1):1; Optionally, the molar ratio of lithium to cobalt of the second lithium source and the second cobalt source is (1.05-1.1):1; Optionally, the first sintering conditions include: heating the first mixture to 500°C to 900°C at a heating rate of 2°C / min to 10°C / min, keeping the temperature for 4h to 8h, and then heating the first mixture to 1000°C to 1200°C at a heating rate of 2°C / min to 5°C / min, and keeping the temperature for 7h to 12h; Optionally, the second sintering conditions include: heating the second mixture to 400°C~800°C at a heating rate of 2°C / min~10°C / min, keeping it warm for 3h~7h, and then heating it to 900°C~1000°C at a heating rate of 2°C / min~5°C / min, and keeping it warm for 5h~9h.

7. The preparation method according to claim 6, characterized in that: Meet one or more of the following conditions: (1) The first mixture further includes a compound containing a first doping element, and the first doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo; Optionally, in the first mixture, based on the mass of the first cobalt source, the content of the first doping element is 500ppm to 15000ppm; (2) the second mixture further includes a compound containing a second doping element, wherein the second doping element is selected from one or more of Mg, Al, Ti, Ca, Sr, Ga, Ge, In, Zr, Ni, Mn, Y, La, W, V, Nb, Ce and Mo; Optionally, in the second mixture, based on the mass of the second cobalt source, the content of the second doping element is 500ppm~12000ppm.

8. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 3 or the positive electrode material prepared by the preparation method according to any one of claims 4 to 7.

9. A lithium ion battery, characterized in that: Including the positive electrode sheet as claimed in claim 8.

10. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Patent Citations

  • Lithium ion battery and its positive material

    CN102394295A

  • Lithium cobalt oxide positive electrode material and preparation method thereof

    CN115995548A

  • Positive electrode material and preparation method and application thereof

    CN117996085A

  • Positive electrode active material, positive electrode, and battery

    JP2006331942A

Cited By

  • Lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery

    CN120565653A

  • Lithium aluminum titanium phosphate compound coated modified lithium cobalt oxide positive electrode material and preparation method thereof

    CN121282139A